β-Adrenergic Receptor Desensitization/Down-Regulation in Heart Failure: A Friend or Foe? - Mahmood, Abrahim; Ahmed, Kinza; Zhang, Youhua (Frontiers in Cardiovascular Medicine, 2022)
Cardiac sympathetic activation, mediated by β-adrenergic receptors (β-ARs), normally increases cardiac contraction and relaxation. Accomplishing this task requires a physiological, concerted Ca2+ signaling, being able to increase Ca2+ release from sarcoplasmic reticulum (SR) in systole and speed up Ca2+ re-uptake in diastole. In heart failure (HF) myocardial β-ARs undergo desensitization/down-regulation due to sustained sympathetic adrenergic activation. β-AR desensitization/down-regulation diminishes adrenergic signaling and cardiac contractile reserve, and is conventionally considered to be detrimental in HF progression. Abnormal Ca2+ handling, manifested as cardiac ryanodine receptor (RyR2) dysfunction and diastolic Ca2+ leak (due to sustained adrenergic activation) also occur in HF. RyR2 dysfunction and Ca2+ leak deplete SR Ca2+ store, diminish Ca2+ release in systole and elevate Ca2+ levels in diastole, impairing both systolic and diastolic ventricular function. Moreover, elevated Ca2+ levels in diastole promote triggered activity and arrhythmogenesis. In the presence of RyR2 dysfunction and Ca2+ leak, further activation of the β-AR signaling in HF would worsen the existing abnormal Ca2+ handling, exacerbating not only cardiac dysfunction, but also ventricular arrhythmogenesis and sudden cardiac death. Thus, we conclude that β-AR desensitization/down-regulation may be a self-preserving, adaptive process (acting like an intrinsic β-AR blocker) protecting the failing heart from developing lethal ventricular arrhythmias under conditions of elevated sympathetic drive and catecholamine levels in HF, rather than a conventionally considered detrimental process. This also implies that medications simply enhancing β-AR signaling (like β-AR agonists) may not be so beneficial unless they can also correct dysfunctional Ca2+ handling in HF.